Evaluating arrhythmias in ECG signals using wavelet transforms. - Addison, P.S.
Recent work has attempted to utilize wavelet techniques in the analysis of biomedical signals including ECGs. Here, the authors present an energy-based method of interrogating the ECG in VF using high-resolution, log-scale continuous wavelet plots. With this method, underlying structures within the VF waveform are made visible in the wavelet time-scale half space.
Keywords: ECG signals; Arrhythmias evaluation; Biomedical signals analysis; Electrodiagnostics; Energy-based method; High-resolution log-scale continuous wavelet plots; Wavelet time-scale half space